Serum Ferritin and Oxidative Stress Markers as Indicators of Disease Progression in Chronic Liver Disease. - Abdul Aziz, Tuba Azam, Sohaib Farooq, Zahid Rashid, Muhammad Adnan Sadiq, Ambreen Zeeshan, Hawaida Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Serum ferritin has emerged as a marker of iron storage and inflammation, while oxidative stress is increasingly implicated in hepatic injury and fibrosis advancement. This case-control observational study aimed to evaluate the relationship between serum ferritin, selected oxidative stress markers (malondialdehyde [MDA], protein carbonyls [PC], total antioxidant capacity [TAC]), and disease severity in patients with chronic liver disease (CLD).